Impact of Soil Test Based Fertilizer Application on Yield, Soil Health and Economics in Rice - Jayalakshmi, M.; Prasadbabu, G.; Chaithanya, B. H.; Bindhupraveena, R.; Srinivas, T. (Indian Journal of Extension Education, 2021)
Frontline demonstrations were carried out to study the soil test-based fertilizer application on yield, soil health and economics in rice during the kharif seasons of 2017, 2018 & 2019Â in farmersâ€™ fields of Kurnool district of Andhra Pradesh. The demonstrations conducted in ten locations revealed that application of nitrogen, phosphorus and potassium based onÂ soil test values resulted in an average yield increase of 5.01 per cent over the farmerâ€™s practice. Demonstration plots recorded an average B: C ratio of 2.9 against farmersâ€™ practiceÂ of 2.4 and the technology index reduced from 3.84 to 1.53 per cent. The organic carbon content increased from 0.45 to 0.50 per cent due the application of farmyard manure basedÂ on soil test value. The soil test based fertilizer application resulted in higher yield, net returns, B:C ratio and organic carbon content and low technology index indicates theÂ feasibility of technology to adopt at farmersâ€™ level.